Experimental study on thermal management of lithium-ion battery with graphite powder based composite phase change materials covering the whole climatic range. (5th November 2022) - Wang, Zichen; Du, Changqing; Qi, Rui; Wang, Yijin
Highlights: The binary and ternary composites for battery thermal management are proposed. The temperature dependence of battery performance is experimentally investigated. The critical temperature for battery insulation and preheating is proposed. The thermal management effects of the composites are compared and evaluated. The ternary composite shows better at thermal management. Abstract: In order to ensure the normal operation of lithium-ion battery in any climate environment, it is necessary to explore the temperature dependence of lithium-ion battery performance, and adopt an effective and low energy thermal management system to maintain the temperature of lithium-ion battery within the normal operating temperature range. In this paper, the temperature dependence of heat generation behavior and charge–discharge performance of lithium-ion battery was studied, and the critical temperature of heat preservation and preheating process was determined. On this basis, graphite powder/paraffin composite phase change material and graphite powder/paraffin/nickel foam ternary composite phase change material with optimized composition were prepared. The thermal management experiment of large-capacity rectangular lithium iron phosphate battery covering the whole climatic range was carried out. The performance of the following thermal management modes was compared: air natural convection, paraffin, graphite powder/paraffin composite, graphite powder/paraffin/nickel foam ternary composite. The experiment showed that the necessary heat dissipation of lithium-ion battery was needed at 20℃ and 40℃ to avoid exceeding the upper limit of normal working temperature. The charge–discharge performance of lithium-ion battery was very sensitive to low temperature environment, especially the battery endurance and charge–discharge capacity. Both graphite powder/paraffin and graphite powder/paraffin/nickel foam composites can effectively control the surface temperature rise of lithium-ion battery, and keep the surface temperature above 0℃ for at least 40 min in the extremely cold environment of −20℃. They also had similar heating efficiency. However, the ternary composite had better temperature homogeneity in both the high temperature environment of 40℃ and the extremely cold environment of −20℃. The maximum temperature difference of ternary composite in the preheating process was 21.43% lower than that of binary composite.